2019
DOI: 10.1088/1757-899x/553/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Carbonate on the Reduction Process of Nickel Slag from Sulawesi

Abstract: Nickel slag is one of the results of the nickel ore smelting process which is still a waste and has not been used optimally. Considering the amount of nickel slag waste in Indonesia, the effort to utilize it into a more valuable product becomes very important. Therefore, in order to extract the precious metal content in nickel slag, this study aims to analyze the effect of adding sodium carbonate in the reduction process of nickel slag. In this study, the reduction process is carried out using coal as a reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…1 that the three strongest diffraction peaks are forsterite (Mg 2 SiO 4 ), fayalite (Fe 2 SiO 4 ) and enstatite (MgSiO 3 ) compounds. This XRD result is appropriate with previous researchers who have characterized the ferronickel slag [15,18,22]. Moreover, morphological structure and mapping from SEM-EDS analysis, Fig.…”
Section: Characterization Of Ferronickel Slag Residues After Leachingsupporting
confidence: 72%
See 1 more Smart Citation
“…1 that the three strongest diffraction peaks are forsterite (Mg 2 SiO 4 ), fayalite (Fe 2 SiO 4 ) and enstatite (MgSiO 3 ) compounds. This XRD result is appropriate with previous researchers who have characterized the ferronickel slag [15,18,22]. Moreover, morphological structure and mapping from SEM-EDS analysis, Fig.…”
Section: Characterization Of Ferronickel Slag Residues After Leachingsupporting
confidence: 72%
“…Research that has been done to process ferronickel slag waste has been carried out by several researchers, both with pyrometallurgical, hydrometallurgical processes and a mixture of both pyro-hydrometallurgy. Several studies with pyrometallurgical processes are by roasting or reducing ferronickel slag with a mixture of additives NaOH [13], Na 2 CO 3 [18] and Na 2 SO 4 [12]. The roasting process is carried out by adding an additive of Na 2 CO 3 for the decomposition of forsterite and enstatite into magnesium oxide and sodium silicate so that it will facilitate the process of separating precious metals, especially magnesium [4].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The compounds contained in the product from alkali fusion, which is named as a roasted product in this study, are quartz (SiO2), sodium silicate (Na2SiO3), fayalite (Fe2SiO4), and hematite (Fe2O3). The sodium silicate (Na2SiO3) appears to form during the alkali fusion process; this was not identified in the previous study [4]- [5].…”
Section: Resultsmentioning
confidence: 71%
“…Arum Cahyanurani S. et al, [4] reported that the valuable metals in the slag are difficult to be separated due to their bonding in the silica-iron matrix in the fayalite phase, which is a dominant phase in ferronickel slag. Moreover, M. D. Alfariz et.…”
Section: Introductionmentioning
confidence: 99%